Age of first exposure does not relate to post-career health in former professional american-style football players - Terry, D. P.; Grashow, R.; Iverson, G. L.; Atkeson, P.; Rotem, R.; Eagle, S. R.; Daneshvar, D. H.; Zuckerman, S. L.; Zafonte, R. D.; Weisskopf, M. G.; Baggish, A. (Sports Medicine, 2024)
Objective: Prior studies examining small samples of symptomatic former professional football players suggest that earlier age of first exposure (AFE) to American football is associated with adverse later life health outcomes. This study examined a larger, more representative sample of former professional American football players to assess associations between AFE before age 12 (AFE < 12) and clinical outcomes compared with those who started at age 12 or older (AFE 12 +). Methods: Former professional American football players who completed a questionnaire were dichotomized into AFE < 12 and AFE 12 + . AFE groups were compared on outcomes including symptoms of depression and anxiety, perceived cognitive difficulties, neurobehavioral dysregulation, and self-reported health conditions (e.g., headaches, sleep apnea, hypertension, chronic pain, memory loss, dementia/Alzheimer`s disease, and others). Results: Amoal seasons, and past concussion burden revealed no significant relationships between AFE < 12 and any outcome. Linear and non-linear models examining AFE as a continuous variable showed similar null results. Conclusions: In a large cohort of former professional American-style football players, AFE was not independently associated with adverse later life outcomes. These findingsng 4189 former professional football players (aged 52 ± 14 years, 39% self-reported as Black), univariable associations with negligible effect sizes were seen with AFE < 12, depressive symptoms (p = 0.03; ?2 = 0.001), and anxiety-related symptoms (p = 0.02; ?2 = 0.001) only. Multivariable models adjusting for age, race, body mass index, playing position, number of profession are inconsistent with smaller studies of former professional football players. Studies examining AFE in professional football players may have limited utility and generalizability regarding policy implications for youth sports.